Biobanks, governance, and informed consent and individual control - a view from the United States - Wright Clayton, Ellen (Henry Stewart Talks, 2015)
The structure and governance of biobanks, Where data and biospecimens come from, Downstream users of biobanks, How much individual control does one have, The impact of return of individual research results